Development of pick and place system using IRB 1400 robot - Norhayati, Mat Noor (2006)
Many robots have been built for manufacturing purposes and can be found in factories around the world .The idea behind this project is to reduce the utilization of human energy especially in manufacturing industry. The project involves of development pick and place system a using ABB IRB 1400 industrial robot. In this project, the IRB 1400 robot was program to perform pick and place task. The robot was equipped with robotic sensor to detect the work pieces. Using the ABB robot’s Rapid software, the program was downloaded to the robot controller, S4Cplus. By teaching the robot points with the Teach Pendants, we can execute the ABB robot program sequences. In the manufacturing system, conveyor work as a method of work part delivery. Model of small conveyor was constructed to delivery the work pieces from the incoming part. The sensors were mounted to the conveyor, which is to sense the incoming material and also to control the operation of the conveyor motor. The robot that was programmed will pick and place the material in the outgoing part. The operation of the system working continuously since the sensor detected the incoming material.